Wage inequality, comparative advantage and skill biased technical change in South Africa - Jørn Rattsø; Hildegunn Stokke (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
International trade may influence income distribution. This study takes as a starting point the puzzling development of relative wages between skilled and unskilled labor in South Africa. Wage inequality decreased during the sanctions period and increased with trade liberalization post Apartheid, contrary to the standard trade theory prediction for an economy with comparative advantage in unskilled labor. We calibrate a Ramsey growth model for South Africa to clarify and quantify the distributive effects of trade barriers, and offer an understanding of the South African experience based on the interaction between openness and skill biased technical change. The dependence on foreign technology increases with openness and gives higher degree of skill bias, which may explain the observed relative wage path. Our model calibration is an alternative to econometric studies separating between trade and technology effects. A counterfactual analysis shows that without sanctions and protectionism during the 1980s the skilled-unskilled wage gap is about 13% larger on average. The quantitative results imply that an increase in trade as share of GDP of 10% points generates an increase in the wage gap of 6.6%. The analysis reveals a tradeoff between growth and distribution.
Keywords: F16; O33; O41; O55; 330; Wage gap; productivity growth; skill bias; South Africa